Coping with COVID-19, the Mobile Way Experience and Expertise from China - Xu, Xiaoge (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2022)
This edited book examines the impact of COVID-19 on selected areas of mobile studies, ranging from mobile public spaces to mobile workspaces. This book offers insights into how to leverage mobile devices, as well as features and communication to contain the pandemic. Specifically, it highlights the Chinese experience and lessons, and the country's expertise in social capital management during the health crisis, governance of information flow and order, combating fake news and the infodemic, documenting the pandemic, and lessons learned from mobile health communication. It also discusses how small companies can survive the death of foreign trade during the pandemic. Looking beyond the pandemic, the book also explores the challenges and opportunities posed by the pandemic by investigating mobile learning, mobile journalism, mobile marketing and mobile workspaces. Given its scope, this book will enhance the global efforts in fighting the pandemic and contribute to the current body of knowledge on how to leverage mobile technologies to enhance public health communication during public health crises. Xiaoge Xu (BA, BA, MS, PhD) is an Associate Professor of Media and Communication Studies at the University of Nottingham Ningbo China, where he is the founding director of the Institute for Mobile Studies. He is the editor-in-chief of IGI Global's Advances in Wireless Technologies and Telecommunication book series. His research interests include mobile journalism, mobile storytelling, mobile experience, city storytelling, mobile technologies for sustainable development, and mobile learning. .
Chapter 1: Introduction -- Section I: Coping with COVID-19: The WeChat Way -- Chapter 2: "You Wait for Me for a Moment": Mobile Usage of the Elderly Female Adults in China to Cope with COVID-19 -- Chapter 3: COVID-19 Fake News and Older Adults: Predicating News Credibility Evaluation -- Chapter 4: Coping with COVID-19: The WeChat Way -- Section II: Reporting on COVID-19, the Mobile Way -- Chapter 5: Predicting News Engagement on Douyin: The Case of COVID-19 Coverage -- Chapter 6: Reporting COVID-19 via Crowdsourcing: The US vs. China -- Section III Coping with COVID-19: Information Disorder and Personal Privacy -- Chapter 7: Typology and Governance of Information Disorder Related to COVID-19 in China -- Chapter 8: Public Health vs. Personal Privacy during COVID-19 in China -- Section IV: Coping with COVID-19: The Survival Efforts -- Chapter 9: Digital Transformation or New Digital Divide 2.0? -- Chapter 10: Mobile Marketing and Innovation: Saviors for Tourism during the Pandemic -- Chapter 11: From Epicenter to Hero City: How Wuhan Survived the Pandemic -- Section V: Beyond COVID-19: Collaborative Mobile Learning and Mobile Workplaces -- Chapter 12: Collaborative Learning during the Pandemic: The Role of Mobile Devices -- Chapter 13: Mobile Workspaces for the Construction Industry in the Post-COVID-19 Era.
Keywords: Communication in medicine; Communication-Methodology.; Public health; Wireless communication systems; Mobile communication systems; Health Communication; Media and Communication Methods; Public Health; Wireless and Mobile Communication